Pengembangan E-Modul Pada Materi Laju Reaksi Menggunakan Model Pembelajaran Inkuiri Terbimbing Kelas XI MIPA Di SMA Negeri 1 Waigete - Bernadina Petra Elti; Nursina Sya’bania; Kartini Rahman Nisa (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
This research is development research which aims to develop a learning E-Module using a guided inquiry model in reaction rate material to determine the validity, practicality and effectiveness of the E-Module. The development model used in this research uses the ADDIE development model which consists of 5 stages, namely Analyze, Design, Development, Implementation and Evaluation. This E-module has gone through a validation stage by validators/experts and has gone through food trials, resulting in an E-Module that is valid, practical and effective. The results of the research are 1) E-Module validity assessment by material experts obtained a score of 0.77% in the medium validity category, and media experts obtained a score of 0.81% in the high validity category; 2) the assessment of the practicality of the e-module in student responses obtained a score of 83.75% and teachers who obtained a score of 94.64% were categorized as very practical; 3) The assessment of the effectiveness of the E-Module was seen from the learning results test on 20 students and received a score of 94% so it was categorized as very effective. The conclusion is that the development of a learning E-Module using a guided inquiry model in reaction rate material is valid, practical and effective for use in learning.